PENGARUH METODE LATIHAN IMAGERY TERHADAP KETEPATAN SEPAK MULA DALAM PERMAINAN SEPAK TAKRAW - Abdilah, Abdilah; Simanjuntak, Victor G.; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is, is there an influence of imagery training methods on the accuracy of soccer (service) in the soccer takraw game on extracurricular participants in SMP Negeri 20 Pontianak?. The method in this study uses the method of experimental form Pre-Experimental with One-Group Pretest-posttest design. The population was 20 extracurricular students of SMP N 20 Pontianak and a sample of 20 students. The instrument used was a soccer ability test sheet. Data analysis uses t-test analysis (influence test). Based on the calculation of the data obtained by the ability to start (service) with an average pretest result of 11.7 and posttest of 14.3. Then the t-test is calculated to get the tcount in the imagery exercise method is 3.707 and the ttable is 1.729 with a significance level of 5%, which means tcount> ttable. With a percentage increase of 22%. Based on the above calculation, it can be said that Ho is rejected and Ha is accepted, which means that there is an influence of imagery training methods on the accuracy of football (service). Keywords : Imagery Training Method, Accuracy Of Soccer.